Implementasi Peraturan Walikota Medan Nomor 18 Tahun 2021 Tentang Pelimpahan Sebagian Kewenangan Pengelolaan Persampahan Kepada Camat Di Lingkungan Pemerintah Kota Medan - Janres Valentino Nainggolan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Medan Mayor Regulation Number 18 of 2021 concerning the Delegation of Partial Waste Management Authority to Subdistrict Heads within the Medan City Government is a regulation issued with the aim of carrying out the delegation of part of the authority for waste management from the Environmental Service to the District to bring closer and improve waste management and city cleanliness services and with the aim of strictly dividing the roles, duties and functions between the Environmental Service and the Subdistrict so that waste management can be carried out efficiently, effectively and optimally so that the community as service users can be well served and the cleanliness, beauty and sanitation of the city is maintained more optimally. The research method used in this research is descriptive research with a qualitative approach. Data collection was carried out using interview, observation and documentation techniques. The data obtained were analyzed qualitatively using an implementation model, where researchers used four variables, namely policy measures and targets, resources, communication, and social, economic and political environments. The results of the research show that the implementation of Medan Mayor Regulation Number 18 of 2021 in East Medan District is still not optimal. There are still many complaints from the public related to waste problems, including communication carried out by implementors that has not been implemented properly so that the public as service recipients are still not aware of the existence of this regulation. Furthermore, economic, social and political conditions greatly influence the success of implementing this Mayor's Regulation where the community is given the responsibility to provide financial contributions, but its implementation is still not well realized. Several factors that influence the implementation of Medan Mayor Regulation Number 18 of 2021 in East Medan District are also still experiencing obstacles, including the consistency of implementers related to confirming and determining schedules for transporting waste from households.